Big Data Processing in Cloud Computing Environments - Noraziah, Ahmad; Fakhreldin, Mohammed Adam Ibrahim; Khalid, Adam; Mazlina, Abdul Majid (American Scientific Publishers, 2017)
Cloud computing is a powerful technology to perform massive-scale and complex computing. It eliminates the need to maintain expensive computing hardware, dedicated space, and software. Massive growth in the scale of data or big data generated through cloud computing has been observed. Addressing big data is a challenging and time-demanding task that requires a large computational infrastructure to ensure successful data processing and analysis. This paper introduces several Big Data processing techniques from system and application aspects. First, from the view of cloud data management and Big Data processing mechanisms, we present the key issues of Big Data. Following, we present the cloud computing for Big Data and related work. Furthermore, we also discuss, Big Data moving to the cloud. Finally, we present the conclusion and future work.